PERAN TAMAN HUTAN HUJAN TROPIS INDONESIA TERHADAP IKLIM MIKRO (Studi Kasus di Taman Hutan Hujan Tropis Indonesia Kawasan Kantor Gubernur di Kota Banjarbaru Provinsi Kalimantan Selatan) - Fathur Raihan; Arief R. M. Akbar; Eko Rini Indrayatie; Kissinger Kissinger (EnviroScienteae, 2023)
In line with the increasing population and the community's need for city facilities and infrastructure, urban development continues to increase. The paradigm of urban development should have changed and needs to be designed early towards the city with a better, more balanced way of life and still paying attention to environmental quality. The level of environmental comfort decreases as a result of the imbalance between built-up space and green open space (RTH) with the three main functions of urban vegetation being structural function, environmental function and visual function. RTH has a role in shaping the comfort of the urban climate through ecological functions, namely as a regulator of air temperature and humidity, so that it can be used as input in improving the quality of the microclimate by improving the quality of urban RTH so as to minimize the decline in environmental quality. The purpose of the study was to analyze the influence of vegetation structure and the role in improving the microclimate at each Tropical Rainforest Miniature RTH location in the Governor's Office area in Banjarbaru City. Banua Botanical Garden as a research site located in the Banjarbaru City Area, South Kalimantan Provincial Government Office Complex. The influence of vegetation structure on Location I which is dominated by lawns/grasses and shrubs with horizontal and columnar header shapes with low header density. Meanwhile, in Location II, the shape of the canopy is columnar and horizontal with a medium canopy density and has a tree height of 3-4 meters, slightly reducing the air temperature around the RTH. For Locations III and IV, they have a pyramid-shaped and spherical header shape that acts as a counterweight to increasing air humidity and decreasing air temperature.  The role of the Tropical Rainforest Miniature RTH in the Governor's Office area in Banjarbaru City in improving the microclimate based on air temperature at locations I, II, III and IV, namely 30.1°C, 29.2°C, 28.0°C and 27.3°C.  It can be seen that location III and location IV have the lowest temperature because they have characteristics of vegetation structures that can lower air temperature. For humidity parameters, it will adjust to air temperature conditions as well as wind speed will adjust to the vegetation structure in the RTH.